Study of temperature variation in cortical bone during osteotomies with trephine drills - Gehrke, Sergio Alexandre; Pazetto, Marcelo Khoury [UNESP]; Oliveira, Sergio de [UNESP]; Corbella, Stefano; Taschieri, Silvio; Mardegan, Fabio E. C. [UNESP] (Springer, 2014)
The purpose of this study was to compare temperature variation during osteotomies with trephine drills under different irrigation conditions: without irrigation, external irrigation, and double irrigation.Synthetic blocks of bone (type I density) were used for drilling procedures with an experimental computed machine, which measured the maximum temperature in the cortical bone during osteotomy with a bone cut that was 5 mm in both diameter and depth. Three groups were formed depending on the irrigation conditions: no irrigation (G1), external irrigation (G2), and double irrigation (G3). Fifty drillings were performed for each group.The average thermal increase in the groups was 21.7 +/- 1.52 A degrees C in G1, 14.2 A +/- 0.70 A degrees C in G2, and 12.4 A +/- 0.75 A degrees C in G3. The results presented statistically significant differences among all groups (alpha = 0.05).The double irrigation technique resulted in a smaller increase in temperature in the cortical bone model, demonstrating a greater efficiency, which may be beneficial when compared to external irrigation alone.The trephine has been widely used in removing small blocks for bone graft, especially the posterior mandible, where the possibility of heating may be higher due to the density of cortical bone in this area. So it is important that the professionals select instruments that can reduce the risks of complications in the proposed treatment.
Keywords: Trephine drill; Osteotomy; Bone surgery; Irrigation methods; Thermocouple